An Assessment of the Relationship Between Essential Hypertension with Nfkb Transcription Factor and Antioxidant Parameters - Odeyinka Odewusi; Chinwe Uzowa; Farouk Adetunji; Olayinka Olaniyan; Olalere Obadire; Zainab Sokunbi (AlQalam Journal of Medical and Applied Sciences, 2023)
The mechanisms that are associated with the development and progression of hypertension or high blood pressure have not been totally demystified. As a result of hypertension being associated or linked with the inflammation cascades, this research was designed to determine BMI (body mass index), Systolic and diastolic blood pressure (SBP and DBP), Nuclear Factor Kappa-Light-Chain-Enhancer of Activated B Cells (NF-κB p65), gluthathione peroxidase (GPx) and 8-hydroxy-2′-deoxyguanosine (8OHdG) in Hypertensive subjects relative to control. A total of one hundred and (185) subjects, of which, sixty five (65)and sixty (60) subjects were treated and newly diagnosed essential hypertensive subjects respectively while the remaining sixty (60) subjects were apparently healthy subjects without hypertension were used as control samples. Statistical analysis was done using SPSS, ANOVA was the tool of choice in comparing means, and all values were significant at p˂ 0.05. In this research, DBP, SBP, NF-κB P65 and 8OHdG were significantly higher while GPx was lower in both treated and newly diagnosed hypertensive subjects compared with control. A significant higher variation in DBP, SBP, NF-κB P65, 8OHdG and GPx was observed in newly diagnosed hypertensive subjects when compared with treated hypertensives. It appears activation of the inflammation Cascades through the NF-κB pathway together with oxidative stress and oxidative DNA are associated with essential hypertension. Furthermore the beneficial effect of treatment in the form of Diet, Lifestyle modifications and antihypertensive drugs can be described as incontrovertible. These findings could help in designing better testing and treatment strategies to get better clinical outcomes.